An Academic Occupation: Mobilisation, Sit-In, Speaking Out and Confrontation in the Experiences of Māori Academics - Mercier, Ocean Ripeka; Asmar, Christine; Page, Susan (The Australian Journal of Indigenous Education, 2011)
Māori and other Indigenous scholars have been calling for the Indigenisation of academic space for decades. But what is the day-to-day experience of Māori academics within Aotearoa–New Zealand universities, and how does this experience reveal or enact the commitments to claim space? We interviewed 12 Māori academics and analysed and organised their experiences in the following way: the university can be understood as a site of (1) mobilisationof Māori staff and students; (2) sit-in, or infusing the institutional system with Indigenous values; (3) speaking out, thereby educating not only students, but staff and the public about Indigenous issues; and (4) at which confrontationis part of the academic terrain. The most common outcome of confrontationwas negotiationand reclamationof space for Māori people, norms and values. In spite of this apparent willingness of the university to compromise, we find that capitulation(being moulded to the norms of the academy) and ( self-)eviction(reconciling difference by leaving the university) are ever-present possibilities for Māori academics. In shaping and presenting the Māori academic occupation as a 4-stage commitment to affirm Māori identity, norms and scholarship, we present a framework within which Indigenous and minority academic work may be understood.